Random amplified polymorphic DNA (RAPD) and random amplified microsatellite (RAMS) of Ganoderma from infected oil palm and coconut stumps in Malaysia - Zakaria, Latiffah; Kulaveraasingham, Harikrishna; Tan, Soon Guan; Abdullah, Faridah; Ho, Yin Wan (Malaysian Society for Molecular Biology and Biotechnology, 2005)
Random amplified polymorphic DNA (RAPD) and random amplified microsatellite (RAMS) analyses were used to determine the genetic relatedness within and between Ganoderma boninense isolates from infected oil palm and Ganoderma sp. from coconut stumps from different locations in Malaysia. RAPD analysis using four random primers (5'ACCTGGACAC3', 5'CAGCGACAAG3', 5'AGAGGGCACA3' and 5'TGACGGCGGT3') showed variations of banding patterns within and between the isolates from oil palm and coconut stumps, indicating that they were genetically heterogeneous. There was no specific banding pattern that could differentiate between G. boninense isolates from infected oil palm and Ganoderma sp. from coconut stumps. RAMS analysis using four microsatellite primers, 5'BDB(ACA)5, 5'DD(CCA)5, 5'DHB(CGA)5 and 5'YHY(GT)5G, also showed variable banding patterns among the isolates from infected oil palm and coconut stumps. However, five common bands i.e. two bands (900 bp and 1200 bp) produced by primer (CGA)5, one band (1400 bp) by primer (ACA)5 and two bands (350 bp and 380 bp) by primer (CCA)5 were shown by all the G. boninense isolates from infected oil palm and Ganoderma sp. from coconut stumps. Dendrograms from cluster analysis based on UPGMA of RAPD and RAMS data showed that G. boninense isolates from infected oil palm and Ganoderma sp. from coconut stumps did not cluster separately into two distinct clusters, but were clustered together, which indicated that both groups of Ganoderma are closely related. The finding that the Ganoderma isolates from coconut stumps are closely related to G. boninense isolates from infected oil palm would have an important bearing in the formulation of disease control measures and replanting procedures, especially in areas where the previous crop was coconut.